The Peranakan Baba Nyonya culture: Resurgence or disappearance? - Lee, Su Kim (Universiti Kebangsaan Malaysia, 2008)
Hybridity of cultures can take many forms and permutations, including the borrowing of words and the adoption of social practices and beliefs, and the adaptation of dress and food. Patterns of migration and cultural flows in Southeast Asia have generated at different times and places all the above configurations and more. Under certain circumstances, what may emerge is a whole new ethnic group or at the very least, a very recognizably different subgroup of an existing ethnic category. One such group is the peranakan or the baba nyonya community (also known as the Straits Chinese). It evolved in the fifteenth century when the Chinese arrived in Malacca and intermarriage with local women took place. The peranakan culture is a unique blend of two cultures – Malay and Chinese – intermixed into a fascinating synthesis with elements of Javanese, Batak, Thai and British cultures, representing “multiculturalism” and “fusion”, long before the terms were invented. Today, the world of the peranakan is a disappearing one